Efficacy and safety of polyethylene glycol loxenatide in treating mild-to-moderate diabetic kidney disease in type 2 diabetes patients: a randomized, open-label, clinical trial - Cao, YongSheng; Cao, Shujie; Zhao, Jiangang; Zhao, Jianqin; Zhao, Yanan; Liu, Ying (Frontiers in Endocrinology, 2024)
This study aimed to evaluate the efficacy and safety of polyethylene glycol loxenatide (PEG-Loxe) compared to those of dapagliflozin in patients with mild-to-moderate diabetic kidney disease (DKD), a prevalent microvascular complication of type 2 diabetes mellitus (T2DM). The study is set against the backdrop of increasing global diabetes incidence and the need for effective DKD management.This study constituted a single-center, randomized, open-label, clinical trial. The trial included patients with mild-to-moderate DKD and suboptimal glycemic control. Eligible participants were randomly allocated to one of the two groups for treatment with either PEG-Loxe or dapagliflozin. The primary endpoint was the change in UACR from baseline at 24 weeks.Results: Overall, 106 patients were randomized and 80 patients completed the study. Following 24 weeks of treatment, the PEG-Loxe group exhibited a mean percent change in baseline UACR of -29.3% (95% confidence interval [CI]: -34.8, -23.7), compared to that of -31.8% in the dapagliflozin group (95% CI: -34.8, -23.7). Both PEG-Loxe and dapagliflozin showed similar efficacy in reducing UACR, with no significant difference between the groups (p = 0.336). The HbA1c levels decreased by -1.30% (95% CI: -1.43, -1.18) in the PEG-Loxe group and by -1.29% (95% CI: -1.42, -1.17) in the dapagliflozin group (p = 0.905). The TG levels decreased by -0.56 mmol/L (95% CI: -0.71, -0.42) in the PEG-Loxe group and -0.33 mmol/L (95% CI: -0.48, -0.19) in the dapagliflozin group (p = 0.023). Differences in TC, HDL-C, LDL-C, SBP, and DBP levels between the groups were not statistically significant (all p > 0.05). Safety profiles were consistent with previous findings, with gastrointestinal adverse events being more common in the PEG-Loxe group.Conclusions: PEG-Loxe is as effective as dapagliflozin in improving urine protein levels in patients with mild-to-moderate DKD and offers superior benefits in improving lipid profiles. These findings support the use of PEG-Loxe in DKD management, contributing to evidence-based treatment options.Clinical trial registration: www.chictr.org.cn, identifier ChiCTR2300070919.